Weather Elements and Frost Occurrence in Arid Zone of Haryana - Satyawan, Satyawan; Niwas, Ram; Khichar, M L (Annals of Arid Zone, 2016)
The study was conducted at CCS Haryana Agricultural University Hisar. The daily meteorological data of winter seasons (December to February) of past 20 years from 1982 to 2002 were used. Mean frosty days were maximum in January (12.7) followed by December (8.5) and February (5.7). The CV was less in January as compared to December and February. Maximum probability of frost occurrence was 0.70 on 24th January. Grass minimum temperature was correlated with weather parameters of two preceding days. Grass minimum temperature was significantly correlated with minimum temperature; morning and. evening actual vapor pressure and morning and evening relative humidity. Minimum temperature and morning actual vapor pressure of previous day (logarithmic relationship) individually explained the variability in grass minimum temperature of next day up to 76%. Key words: Frost, grass minimum temperature.